Contemporary review of the organ care system in lung transplantation: potential advantages of a portable ex-vivo lung perfusion system - Schmack, Bastian; Weymann, Alexander; Mohite, Prashant; Saez, Diana Garcia; Zych, Bartlomiej; Sabashnikov, Anton; Zeriouh, Mohamed; Schamroth, Joel; Koch, Achim; Soresi, Simona; Ananiadou, Olga; Robertis, Fabio De; et al. (Expert review of medical devices, 2016)
Lung transplantation remains the definite treatment for various end-stage lung diseases. Cold flush perfusion, the standard method for organ procurement has severe limitations. Organ Care System (OCS; TransMedics, Inc., Andover, USA) is an approved method to preserve hearts for transplantation that allows for greatly reduced cold ischemic time. Consequently, the use of an adapted OCS lung as a portable full ex-vivo lung perfusion system in lung transplantation is currently under close evaluation. Areas covered: The aim of this article is to review the advantages and the role of the OCS in the field of lung transplantation by reviewing the latest literature and evaluating this novel procurement technique in the context of conventional methods like cold flush and regular ex-vivo lung perfusion.
Gesehen am 15.05.2020